2019
DOI: 10.4254/wjh.v11.i5.450
|View full text |Cite
|
Sign up to set email alerts
|

Expanding etiology of progressive familial intrahepatic cholestasis

Abstract: BACKGROUND Progressive familial intrahepatic cholestasis (PFIC) refers to a disparate group of autosomal recessive disorders that are linked by the inability to appropriately form and excrete bile from hepatocytes, resulting in a hepatocellular form of cholestasis. While the diagnosis of such disorders had historically been based on pattern recognition of unremitting cholestasis without other identified molecular or anatomic cause, recent scientific advancements have uncovered multiple specific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 82 publications
1
119
0
3
Order By: Relevance
“…FIC1 is part of the type 4 subfamily of P-type adenosine triphosphatases, which are involved in translocating phospholipids in membranes[ 18 ]. This protein, present at the apical membrane of hepatocytes, is thought to function as an aminophospholipid translocase, carrying phospholipids, specifically phosphatidylserine (PS) and phosphatidylethanolamine (PE), from the outside, ectoplasmic leaflet of the canalicular membrane, to the inside, cytoplasmic leaflet in hepatocytes[ 17 - 19 ]. When functioning normally, FIC1 protects the hepatocyte from high bile salt concentrations[ 17 ].…”
Section: Pficmentioning
confidence: 99%
See 1 more Smart Citation
“…FIC1 is part of the type 4 subfamily of P-type adenosine triphosphatases, which are involved in translocating phospholipids in membranes[ 18 ]. This protein, present at the apical membrane of hepatocytes, is thought to function as an aminophospholipid translocase, carrying phospholipids, specifically phosphatidylserine (PS) and phosphatidylethanolamine (PE), from the outside, ectoplasmic leaflet of the canalicular membrane, to the inside, cytoplasmic leaflet in hepatocytes[ 17 - 19 ]. When functioning normally, FIC1 protects the hepatocyte from high bile salt concentrations[ 17 ].…”
Section: Pficmentioning
confidence: 99%
“…In hepatocytes, elevated bile salts concentrations activate FXR, which induces the expression of the BSEP[ 17 , 19 ]. BSEP allows for the pumping of bile salts out of the hepatocyte into the canalicular lumen[ 17 , 19 ]. Additionally, when expressed in the intestines, FXR represses the expression of ASBT.…”
Section: Pficmentioning
confidence: 99%
“…39 A systematic review reported that SAM improves some liver biochemical parameters and symptoms in patients with intrahepatic cholestasis, 40 which is a feature of several CLDs. 41 Furthermore, in recent years, N 6 -methyladenosine (m 6 A) modifications have been proven to be related to liver injuries. Deregulation of m 6 A regulators in host hepatocytes may contribute to the development of viral hepatitis.…”
Section: The Physiological Role Of Methionine Metabolismmentioning
confidence: 99%
“…Why there was a similar fall in age at LT in siblings with SLD is not clear. Siblings with metabolic SLD may have a discordant phenotype, 3,4 but this should result in variability in age at LT rather than a progressive fall. One factor may be that when families, and their physicians, see the benefit of LT in one sibling, they are more proactive about embracing LT before deterioration, with associated complications, occurs in another.…”
Section: Discussionmentioning
confidence: 99%